PENGARUH RASIO KEUANGAN TERHADAP PREDIKSI FINANCIAL DISTRESS (Studi pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di BEI Periode 2015 – 2018) - Erna Ismiati; Edi Wibowo; Setyaningsih Sri Utami (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
The objective of this research was to analyze the significance the effect of ROA, ROE, NPM, and PER partially and simultaneously on financial distress. The population was all manufacture companies Aneka Industry’s Sector listed on the Indonesia Stock Exchange (BEI) in the period of 2015 – 2018. Based on purposive sampling method, samples obtained are 11 companies so obtain 44 observations. The data were secondary data obtained from financial statement. Methods of data analyzed by using multiple linear regression analysis assisted with an SPSS version 20 software program. The result of the research showed that ROA had positive significant influence on financial distress. ROE had negative significant influence on financial distress. NPM and PER have no significant influence on financial distress. Simultaneously ROA, ROE, NPM and PER significantly influence financial distress.